Quantifying the components of the banks' net interest margin - Ramona Busch; Christoph Memmel (Deutsche Bundesbank, 2014)
Using unique data sets on German banks, we decompose their net interest margin and quantify the different components by estimating the costs of the various functions they perform. We investigate three major functions: namely, liquidity and payment management for the customers, the bearing of credit risk, and term transformation. For the year 2012, the costs of liquidity and payment management correspond, in the median, to 47%, the bearing of credit risk to 16%, and earnings from term transformation to 35% of the net interest margin, respectively. However, looking at the period 2005-2012, earnings from term transformation seem to account for a much smaller share (about 20%) of the median bank's net interest margin.
Keywords: G21; 330; net interest margin; credit risk; term transformation; liquidity and payment management